Analisis Kebutuhan Pengembangan Majalah Kimia pada Materi Reaksi Aldol Silang di Perguruan Tinggi - Syarifa Wahidah Al Idrus; Rahmawati Rahmawati (YASIN, 2026)
This study was motivated by the need to develop innovative, visual, and concise learning media to support students’ understanding of the aldol reaction topic in the Mechanisms and Synthesis of Organic Compounds (MSSO) course. This study aims to analyze the need for developing a chemistry magazine on the topic of aldol reactions, particularly crossed aldol reactions. This descriptive study with a mixed-method approach involved 31 Chemistry Education students at the University of Mataram from the 2022 cohort who had taken the MSSO course. The research instruments included a needs analysis questionnaire consisting of nine questions, semi-structured interview guidelines for three informants, and a document analysis sheet. Quantitative data were analyzed using descriptive percentages, whereas qualitative data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that all students (100%) experienced difficulties in understanding the mechanism of crossed aldol reactions, while the available learning media, namely PowerPoint presentations and textbooks, were considered ineffective by 100% of respondents. In addition, 93.5% of students strongly agreed that a chemistry magazine was the desired learning medium. Students’ preferences for reading supplements included colorful layouts (87.1%), a combination of text and images (90.3%), and a communicative language style (83.9%). These findings indicate a gap between students’ need for innovative, visual, and concise reading supplements and the reality of learning, which still relies on conventional media. The conclusion of this study affirms that the results of the needs analysis serve as an important basis for developing a chemistry magazine on crossed aldol reaction material as a valid, practical, and effective reading supplement.